Trade and exchange in the Southern Levant in the 13th Century BCE: a view from Tel Burna, a Town in the Shephelah, Israel - Shai, Itzhaq (2018)
The excavations at Tel Burna (southern Israel) have exposed a large public building where cultic activity took place. The fi nds that were recovered in this complex include imported artifcats from the eastern Mediterranean. In this paper, we will present these fi nds and discuss how they refl ect trade and foreign connections with the eastern Mediterranean to the Southern Levant in the 13th century BCE, as well as their importance for understanding the local material culture and ritual activity.